Experimental and Numerical Investigation of High Strength Reinforced Concrete Deep Beams with Web Openings under Repeated Loading - Al-Shaarbaf, Ihsan A. S.; Ali, Ahmed s.; Abdulridha, Abdulkhalik J. (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper presents experimental investigations to study the behavior of High Strength Reinforced Concrete (HSRC) deep beams with web openings under monotonic and static repeated loading conditions. The experimental work procedure consisted of testing eighteen simply supported HSRC deep beams both with and without web openings. The numerical work procedure consisted of testing ten simply supported HSRC deep beams both with web openings. All beams had the same dimensions and flexural reinforcement. They had an overall length of 1400 mm, a width of 150 mm and a height of 400 mm. The investigated test parameters were concrete compressive strength, shape and size of openings, vertical and horizontal reinforcement ratios, shear span to effective depth ratio (a/d ratio) and loading history. The experimental results reveal that the ultimate load capacities for specimens tested under four different repeated loading regimes decrease in the range between 2% and 19% in regards to the control specimens which were tested under monotonic loading regime.  The results indicated that the increase in the severity of loading history leads to a decrease in the ultimate shear strength of the deep beams and causes increases in their ductility ratio. The ultimate loads of HSRC deep beams with square web openings size of (50*50mm, 60*60mm and 70*70mm) tested under the repeated loading history (HS-1) which consisting of five phases decreased by (11.4 %, 24.1% and 26.3 %, respectively)  compared to that of identical solid deep beam. The ultimate load of HSCR deep beam with circular web openings shape tested under repeated loading history (HS-1) increases by 8.6 % compared to the equivalent square web openings shape. For numerically analyzed beams under repeated loading history (HS-1), the ultimate load increases by 16% when using area of 2500mm2 of circular web openings shape (equal in area to square web opening size 50mm*50mm) and by 13.5% when using rhombus web openings shape of the dimensions 50*50mm in comparison with the case of 60-mm size square web openings.